Feldspathic and Lithium Disilicate Onlays with a 2-Year Follow-Up: Split-Mouth Randomized Clinical Trial - Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP] (2021)
The present study was a prospective, controlled, randomized, clinical short-term trial aiming to evaluate the clinical performance of adhesively luted, lithium disilicate and feldspathic glass-ceramics onlays over a period up to 2 years. A total of 11 patients (7 female, 4 male; age range: 18-60 years, mean age: 39 years) were selected for this study. Each patient received a maximum of two restorations per group in a split-mouth-design. LD: Eleven onlays, performed with lithium disilicate-based ceramic (IPS e.max CAD, Ivoclar Vivadent, Schaan, Liechtenstein), and FP: Eleven onlays, performed with feldspathic ceramic (Vita Mark II, Vita Zanhfabrik, Bad Säckingen). Recalls were performed at 2 weeks (baseline = R1), 1 year (R2) and 2 years (R3) after the cementation by three calibrated blinded independent investigators using mirrors, magnifying eyeglasses, probes and bitewing radiographs. The postoperative sensitivity, secondary caries, marginal integrity, marginal discoloration, color match, surface roughness, tooth integrity, and restoration integrity were evaluated. The Friedman test was used to determine if there was a statistically significant difference in time-to-time comparison of the parameters in the ceramics restorations. A total of 95.4% of the restorations were clinically acceptable at the 2-year recall, without a difference for any evaluation parameter for both ceramic materials. Based on the 2-year data, the CAD-CAM onlays manufactured with feldspathic and lithium-disilicate based ceramics showed similar clinical performance.